The Feeding Value of Toasted Mucuna Seed Meal Diets for Growing Japanese Quail (Coturnix coturnix japonica) - Tuleun, C.D.; Igyem, S.Y.; Adenkola, A.Y. (International Journal of Poultry Science, 2009)
A feeding trial was conducted with two hundred and twenty four one week old quail chicks to study the optimum inclusion level of toasted mucuna seed meal in a practical quail diet. Four isonitrogenous (24% crude protein) diets incorporating graded levels (0, 5, 10 and 15) of toasted mucuna seed meal were formulated and fed for 42 days in a completely randomized design. The chicks were divided into four treatment groups, each group replicated two times with 28 chicks per replicate. A group each was allotted to one of the four isonitrogenous diets. The performance, nutrient digestibility, carcass quality and visceral organs and haematological parameters were evaluated. Feed intake, weight gain, feed/gain ratio and nutrient digestibility did not differ significantly (P>0.05) across the treatments. The haematological parameters of quails fed the mucuna diets were not significantly different (P>0.05) compared to those on control diet. Likewise the inclusion of toasted mucuna seed meal in the diets did not cause significant disproportionate growth in carcass quality and visceral organs. It was concluded that toasted mucuna seed meal can be included up to 15% level in practical diets of growing Japanese quail.